A facile one-step fabrication of novel WO3/Fe2(WO4)3·10.7H2O porous microplates with remarkable photocatalytic activities1. Issue 26 (14th July 2015) - Aslam, Imran; Cao, Chuanbao; Tanveer, M.; Farooq, M. Hassan; Tahir, Muhammad; Khalid, Syed; Khan, Waheed S.; Idrees, Faryal; Rizwan, Muhammad; Butt, Faheem K.
<x xml:space="preserve">Abstract</x> Novel microplates of WO3/Fe2(WO4)3·10.7H2O were synthesized by a one-step hydrothermal technique. The photocatalyst exhibited remarkable photocatalytic activity.